Proceedings of the 5th Workshop on Representation Learning for NLP 2020
DOI: 10.18653/v1/2020.repl4nlp-1.14
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Alignment of Multilingual Models for Extracting Temporal Expressions from Text

Abstract: Although temporal tagging is still dominated by rule-based systems, there have been recent attempts at neural temporal taggers. However, all of them focus on monolingual settings. In this paper, we explore multilingual methods for the extraction of temporal expressions from text and investigate adversarial training for aligning embedding spaces to one common space. With this, we create a single multilingual model that can also be transferred to unseen languages and set the new state of the art in those cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Instead, labeled data from a high-resource language is leveraged. A multilingual model can be trained on the target task in a high-resource language and afterwards, applied to the unseen target languages, such as for named entity recognition Hvingelby et al, 2020), reading comprehension , temporal expression extraction (Lange et al, 2020c), or POS tagging and dependency parsing (Müller et al, 2020). Hu et al (2020) showed, however, that there is still a large gap between low and high-resource setting.…”
Section: Multilingual Language Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, labeled data from a high-resource language is leveraged. A multilingual model can be trained on the target task in a high-resource language and afterwards, applied to the unseen target languages, such as for named entity recognition Hvingelby et al, 2020), reading comprehension , temporal expression extraction (Lange et al, 2020c), or POS tagging and dependency parsing (Müller et al, 2020). Hu et al (2020) showed, however, that there is still a large gap between low and high-resource setting.…”
Section: Multilingual Language Modelsmentioning
confidence: 99%
“…Gui et al (2017), Liu et al (2017), Kasai et al (2019), Grießhaber et al (2020) and learned domainindependent representations using adversarial training. Kim et al (2017), and Lange et al (2020c) worked with language-independent representations for cross-lingual transfer. These examples show the beneficial exchange of ideas between NLP and the machine learning community.…”
Section: Ideas From Low-resource Machine Learning In Non-nlp Communitiesmentioning
confidence: 99%
“…However, a fundamental limitation of existing crosslingual models for REE is the monolingual bias due to the sole reliance on source language data for training. In other NLP tasks, LADV has been explored to address this issue by leveraging unlabeled data in the target language to perform crosslingual representation alignment Huang et al, 2019;Lange et al, 2020;Cao et al, 2020;He et al, 2020). Unfortunately, LADV suffers from the cross-class alignment issue, making it less optimal for crosslingual REE.…”
Section: Related Workmentioning
confidence: 99%
“…However, previous work on crosslingual REE suffers from the monolingual bias issue due to the monolingual training of models on only the source language data, leading to non-optimal crosslingual performance. A solution for this issue can resort to language adversarial training Huang et al, 2019;Keung et al, 2019;Lange et al, 2020;He et al, 2020) where unlabeled data in the target language is used to aid crosslingual representations via fooling a language discriminator. The underlying principle for this approach is to encourage the closeness of representation vectors for sentences in the source and target languages (i.e., aligning representation vectors).…”
Section: Introductionmentioning
confidence: 99%
“…(Lee et al, 2014;Zhong and Cambria, 2018). There are only a small number of fully supervised approaches in this field (Laparra et al, 2018;Lange et al, 2020), and despite the recent rise of transformer-based language models and their ability to generalize well, only the subtask of temporal tagging has been approached with this sort of architecture . One limiting factor for an end-to-end supervised model is the amount of labeled data it requires, which is not necessarily satisfied by the available resources.…”
Section: Introductionmentioning
confidence: 99%